2020
DOI: 10.3390/molecules25225410
|View full text |Cite
|
Sign up to set email alerts
|

Binding Studies of AICAR and Human Serum Albumin by Spectroscopic, Theoretical, and Computational Methodologies

Abstract: The interactions of small molecule drugs with plasma serum albumin are important because of the influence of such interactions on the pharmacokinetics of these therapeutic agents. 5-Aminoimidazole-4-carboxamide ribonucleoside (AICAR) is one such drug candidate that has recently gained attention for its promising clinical applications as an anti-cancer agent. This study sheds light upon key aspects of AICAR’s pharmacokinetics, which are not well understood. We performed in-depth experimental and computational b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 34 publications
4
19
0
Order By: Relevance
“…This result confirms conformational changes in proteins and corroborates our UV absorbance spectroscopic and fluorescence spectroscopic findings. Our findings are consistent with the previous studies on the interaction of small molecules with BSA. , The intensities and wavelengths corresponding to different fluorescence peaks are shown in Table .…”
Section: Resultssupporting
confidence: 93%
“…This result confirms conformational changes in proteins and corroborates our UV absorbance spectroscopic and fluorescence spectroscopic findings. Our findings are consistent with the previous studies on the interaction of small molecules with BSA. , The intensities and wavelengths corresponding to different fluorescence peaks are shown in Table .…”
Section: Resultssupporting
confidence: 93%
“…The obtained results indicate that stronger complexes were formed with increasing temperature, which means a lower therapeutic effect. Peng made similar conclusions in the study concerning the interaction between coenzyme Q 10 and human serum albumin and Hashempour in analyzing the interaction between HSA and 5-aminoimidazole-4carboxamide ribonucleoside [3,47]. They observed that the K SV value increases with temperature.…”
Section: The Fluorescence Analysis Of Effect Of Fatty Acids and Tempesupporting
confidence: 54%
“…The Stern–Volmer analysis ( F 0 / F vs conc.) yielded positive deviations at all three temperatures (Figure B), indicating the presence of transient intermolecular collision (dynamic) and stable binding (static) modes of interactions. These results suggest that albumin may serve as a solubilizer of ADO in the crystalline suspension (Figure ) and may be considered a method for producing cocrystals …”
Section: Resultsmentioning
confidence: 87%